National burden of the pharmaceutical cost of wet compresses and its cost predictors: Nationwide cross-sectional study in Japan - Hiroaki Itoh; Tomoyuki Saito; Shuko Nojiri; Yoshimune Hiratsuka; Kazuhito Yokoyama (Health Economics Review, 2019)
Background: Although a high number of wet compresses are prescribed daily in medical institutions in Japan, our understanding of the national burden of the cost of wet compresses and the details regarding their prescription is far from complete. We investigated the national burden of the annual pharmaceutical cost of wet compresses prescribed in Japan and estimated the predictors of this cost using nationwide health insurance claims data. Methods: We extracted the records on wet compress products from summary table files obtained from the second version of the 'NDB Open Data Japan' website and calculated the annual pharmaceutical cost of wet compresses by patients' 5-year age group, sex, and prefecture. We also conducted an ecological study treating each prefecture as an individual unit and multiple linear regression analyses using the age-standardized cost of wet compresses per resident as a dependent variable. Results: The annual pharmaceutical cost of wet compresses prescribed in Japan in fiscal year 2015 was 149.0 billion Japanese yen (1.18 billion euros; 1.33 billion USD). Multiple linear regression analyses showed that the number of orthopedists and rehabilitation physicians per 100,000 residents were significantly positively associated with the annual pharmaceutical cost of wet compresses per resident (P = 0.042 and P = 0.008, respectively). Conclusions: The annual pharmaceutical cost of wet compresses prescribed in Japan has a considerable impact on the nation's limited healthcare resources. The number of orthopedists and rehabilitation physicians per 100,000 residents may be independent predictors of the wet compress cost in Japan.
Keywords: 330; National database; Health insurance claims; Receipt; Wet compress; Poultice; Cost